KAJIAN PENAFSIRAN DARI MUFASSIR MODERN SEPERTI QURAISH SHIHAB, SAYYID QUTB, ATAU FAZLUR RAHMAN DALAM MELIHAT RELEVANSI AYAT-AYAT PENDIDIKAN UNTUK KONTEKS KEKINIAN - Siti Khotimah; Muhammad Abdul Sidiq; Ainal Ghani; Guntur Cahaya Kesuma; A.Fatoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the interpretation of educational verses in the Qur’an by prominent modern Muslim scholars such as Quraish Shihab, Sayyid Qutb, and Fazlur Rahman, focusing on their relevance to contemporary educational contexts. The problem underlying this research lies in the gap between classical interpretations of Qur’anic verses and the urgent need for a contextual approach that addresses today’s challenges in education. The purpose of this study is to analyze how these modern exegetes contextualize Qur’anic guidance on knowledge, learning, and values within the framework of current educational issues. Employing a qualitative library research method, the study examines primary works of the selected scholars, supported by secondary references. Data were analyzed through descriptive-analytical techniques to identify similarities and differences in their approaches. The findings indicate that Quraish Shihab emphasizes harmony between revelation and reason to support holistic education, Sayyid Qutb highlights the role of Qur’anic values in forming a spiritual-moral foundation for social transformation, and Fazlur Rahman promotes a double-movement hermeneutics that bridges textual meaning with contemporary needs. These interpretations collectively demonstrate that Qur’anic verses on education are not only timeless but also adaptable to the challenges of digitalization, globalization, and character education. The study concludes that modern tafsir provides a dynamic framework for integrating religious values with modern educational practices, offering significant contributions to Islamic education in the contemporary era.